APLIKASI SISTEM PENDUKUNG KEPEUTUSAN PEMILIHAN KARYAWAN TERBAIK DENGAM METODE FUZZY MULTI ATTRIBUTE DECISION MAKING - Fery Purnama (JURNAL AKADEMIKA)
Selection of the best employees is a matter of decision making using (Fuzzy Multi-Criteria Decision / FMCDM). In this KP, built decision support systems (DSS) selecting the best employees at PT. Eleven Computer Jambi by using criteria such as: discipline, attendance, loyalty, work environment. As for explaining the purpose of decision support systems and DSS was created with the aim to facilitate the Best Selection in PT.Eleven Computer Karayawan Jambi. By doing inputting data- employee assessment data. For Admin will facilitate the efficient processing of data and facilitate the preparation of reports to be provided to the Chairman of the Company. Making The Decision Support System using Borland Delphi 7 Programming supported by Microsoft Access as the database manager.